Review of regulatory requirements in the US, EU and Serbia on software - mobile application as a medical device - state of the art - Vukmirović, Dušan; Stević, Ivana; Odalović, Marina; Krajnović, Dušanka (Archives of Pharmacy, 2022)
The number of software - mobile applications intended for use in the field of people’s health and well-being is constantly increasing. The aim of this review is to compare regulations on software – mobile applications as medical devices in the United States of America (USA), European Union (EU) and Serbia, with reference on the efforts for international harmonization of the regulations. The goal is to increase awareness of the broader healthcare professionals’ (HCPs) audience about this topic. Publicly available information from official regulatory bodies websites was analyzed and synthesized for two regions and one country of interest. The results show differences in regulatory approaches in this area between two biggest medical device markets – the USA and the EU, while regulations in Serbia are being harmonized with the EU. Regulations clearly define criteria that software – mobile application needs to meet to be assessed as a medical device; on the other hand, they leave a number of applications that provide health-related services out of the regulated scope. Based on the increased awareness of regulations, recommendations for future research can be directed towards greater involvement of HCPs in patient counseling and decision making regarding the selection of mobile applications, to prevent the use of inadequate mobile applications and ensure that their patients are correctly using the right applications with positive effects on health and well-being.
Keywords: mobile application; software; medical device; regulation; healthcare professionals